Virus as populations : composition, complexity, quasispecies, dynamics, and biological implications - Domingo, Esteban (Academic Press, 2020)
Explains the fundamental concepts surrounding viruses as complex populations during replication in infected hosts. Fundamental phenomena in virus behavior, such as adaptation to changing environments, capacity to produce disease, and the probability to be transmitted or respond to treatment all depend on virus population numbers. Concepts such as quasispecies dynamics, mutations rates, viral fitness, the effect of bottleneck events, population numbers in virus transmission and disease emergence, and new antiviral strategies are included. The book's main concepts are framed by recent observations on general virus diversity derived from metagenomic studies and current views on the origin and role of viruses in the evolution of the biosphere.